1991
DOI: 10.1212/wnl.41.9.1449
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease rigidity

Abstract: We studied the EMG potentials evoked in the bilateral first dorsal interosseus muscle by electromagnetic stimulation of the corticomotoneuronal descending system in 10 Parkinson's disease patients and in 10 age- and sex-matched normal controls. We selected patients who did not have tremor but had predominant rigidity with asymmetric body involvement. On the rigid side of the PD patients, the threshold to cortical stimulation was lower than on the contralateral side or than normal values. On average, patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
135
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(141 citation statements)
references
References 0 publications
5
135
1
Order By: Relevance
“…For example, TMS studies have shown that there is defective cortico-cortical inhibition in motor cortex excitability (Kleine et al, 2001;Pierantozzi et al, 2001;Ridding et al, 1995). This causes a diffused and increased response in the motor cortex that possibly underlies rigidity (Cantello et al, 1991). In the current study, all of our patients had rigidity in the right upper limb ─ UPDRS scores from 1 to 3.…”
Section: Rigidity Bradykinesia and Hyperactivation In The Primary Mmentioning
confidence: 48%
“…For example, TMS studies have shown that there is defective cortico-cortical inhibition in motor cortex excitability (Kleine et al, 2001;Pierantozzi et al, 2001;Ridding et al, 1995). This causes a diffused and increased response in the motor cortex that possibly underlies rigidity (Cantello et al, 1991). In the current study, all of our patients had rigidity in the right upper limb ─ UPDRS scores from 1 to 3.…”
Section: Rigidity Bradykinesia and Hyperactivation In The Primary Mmentioning
confidence: 48%
“…Studies have shown a loss of cortical excitation and inhibition balance in PD with higher motor system excitability in patients with PD at rest compared with controls most likely the result of reduced intracortical inhibition. 14,15,44 Under tonic muscle contraction, shortened CSP in PD also suggests an enhanced excitability. 14 Inhibition as measured through CSP may be important for suppressing competing motor networks thereby facilitating cortical-basal ganglia loops specified for an intended motor action.…”
Section: Discussionmentioning
confidence: 99%
“…44 CSP durations are usually shorter in PD patients compared with controls and, within PD patients, are shorter on the more affected side compared with the less affected side. 14,45 Both CSP durations and parkinsonian symptoms are sensitive to dopaminergic medication. Similar to the observed effects of high-intensity exercise, CSP durations are prolonged in PD patients after taking levodopa, [45][46][47] apomorphine, 48 and pergolide, 19,49 drugs known to provide effective symptomatic relief of motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes depend on the state of activation, whether tested at rest or during voluntary or involuntary motor activity. Cortical excitability is increased during rest and decreased during voluntary activity corresponding to reduced facilitation (Cantello et al, 1991;Valls-Sole et al, 1994). This concept is inferred from the motor evoked potential (MEP), which is subject to methodological limitations such as phase cancellation (Magistris, Rosler, Truffert, & Myers, 1998).…”
Section: Pathophysiology Of Parkinson's Diseasementioning
confidence: 99%